1998
DOI: 10.1152/ajpheart.1998.275.5.h1865
|View full text |Cite
|
Sign up to set email alerts
|

Coronary endothelial P-selectin in pathogenesis of myocardial ischemia-reperfusion injury

Abstract: We investigated in vivo coronary P-selectin expression and its pathophysiological consequences in a murine model of myocardial ischemia-reperfusion (MI/R) using wild-type and P-selectin deficient (−/−) mice. Coronary P-selectin expression [μg monoclonal antibody (MAb)/g tissue] was measured using a radiolabeled MAb method after 30 min of myocardial ischemia and 20 min of reperfusion. P-selectin expression in wild-type mice was significantly ( P< 0.01) elevated in the ischemic zone (0.070 ± 0.010) compared w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
54
0
3

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 32 publications
3
54
0
3
Order By: Relevance
“…Experimental studies have suggested that monoclonal antibodies against L-selectin and P-selectin [183,184] reduced myocardial necrosis, preserving coronary endothelial function and attenuating neutrophil accumulation in the ischemic and reperfused feline myocardium. In addition, P-selectin deficient mice showed decreased infarct size after 30 min of coronary occlusion and 2 h of reperfusion [185]. In contrast, no difference in infarct size was noted after a 60 min ischemic period [185].…”
Section: The Neutrophilsmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental studies have suggested that monoclonal antibodies against L-selectin and P-selectin [183,184] reduced myocardial necrosis, preserving coronary endothelial function and attenuating neutrophil accumulation in the ischemic and reperfused feline myocardium. In addition, P-selectin deficient mice showed decreased infarct size after 30 min of coronary occlusion and 2 h of reperfusion [185]. In contrast, no difference in infarct size was noted after a 60 min ischemic period [185].…”
Section: The Neutrophilsmentioning
confidence: 99%
“…In addition, P-selectin deficient mice showed decreased infarct size after 30 min of coronary occlusion and 2 h of reperfusion [185]. In contrast, no difference in infarct size was noted after a 60 min ischemic period [185]. In addition, mice with a combined P-selectin and ICAM-1 deficiency demonstrated impaired neutrophil trafficking without a difference in infarct size due to myocardial ischemia and reperfusion [186].…”
Section: The Neutrophilsmentioning
confidence: 99%
“…Recent studies have shown that myocardial ischemia/ reperfusion injury could be suppressed by preventing PMN accumulation by inhibition of P-selectin, L-selectin, ICAM-1, or CD18, which are leukocyte adhesion receptors or cell adhesion molecules. For example, the sizes of myocardial infarcts elicited by ischemia/reperfusion were diminished in P-selectin-deficient, ICAM-1-deficient, or CD18-deficient mice (46,47). In addition, ischemia/ reperfusion-induced PMN infiltration and myocardial infarct size were both diminished in dogs treated with a monoclonal anti-P-selectin Ab (48), and myocardial ischemia/reperfusion injuries were reduced by monoclonal Ab's directed against leukocyte adhesion receptor or cell adhesion molecules (49)(50)(51).…”
mentioning
confidence: 99%
“…It has been indicated that endothelial injury/activation leads to the production of certain factors that release P-selectin of endothelial intracellular storage, which mediates cell adhesion [42,43]. Furthermore, the angiopoietin receptor Tie-2 is expressed exclusively in endothelial cells and promotes anigiogenesis [44,45].…”
Section: Discussionmentioning
confidence: 99%